Troubling a star - L'Engle, Madeleine (New York, N.Y. : Bantam Doubleday Dell Books for Young Readers, 1995)
As she tries to stay alive after being left on an iceberg in the Antarctic, sixteen-year-old Vicky recalls the series of events that brought her to the bottom of the world and involved her in a dangerous mystery.
Originally published: New York : Farrar, Straus, Giroux, 1994.
5.7
Keywords: Antarctica -- Fiction; Mystery fiction